(untitled) (Tanzania Medical Journal, 2025)
Background Obstetric fistula is a significant public health problem that causes severe physical, psychological, and social challenges, resulting in a poor quality of life for affected women. Surgical repair is intended to restore their health and well-being. This study explores the lived experiences of women concerning their quality-of-life following fistula repair in Dar es Salaam, Tanzania Methodology Data was collected using a semi-structured interview guide with ten purposively recruited women who had undergone obstetric fistula repair after six months of treatment in Dar es Salaam. Qualitative content analysis was conducted using a deductive approach for pre-determined codes, and later an inductive method was conducted to capture any new emerging codes. The research study was approved by the Institutional Review Board of the Muhimbili University of Health and Allied Sciences. Results Following surgical treatment, the women recovered from leaking urine and associated odors, enabling them to resume their social, religious and economic activities. Although some women were afraid to be remarry due to mistrust and the fear of the fistula redeveloping, others were able to marry and have children after the repair. Successful fistula treatment dramatically improved the women’s quality of life. Conclusion Obstetric fistula treatment led to a marked improvement in women's quality of life. Successful repair enabled them to regain physical strength, resume sexual relations and childbirth, and reintegrate into social and economic life. Increased community awareness of the treatment's advantages contributed to the enhanced well-being of these women.